Gender, Age and Anxiety as Predictors of Nomophobia in University Students* - Taş, İbrahim; EKER, HALİME (Sakarya Üniversitesi Eğitim Bilimleri Enstitüsü, 2021)
Mobile technologies have become one of the important parts of human life. Smartphones have become the most used technological devices of daily life, with newly added features every day. However, intense and non-functional use of these devices may cause problems. Nomophobia, which is defined as the fear of being without a mobile phone or being unable to be online, has begun to take place in literature as a current phenomenon. The present study discusses the variables of gender, age and anxiety as predictors of nomophobia in university students since the phenomenon is common especially in young people. The study group consists of 372 university students. Personal Information Form, Beck Anxiety Scale and Nomophobia scale were used as data collection tools in the study. Pearson correlational analysis and hierarchical regressions were conducted for data analysis. According to the results obtained from the study, anxiety total scale and subjective anxiety and somatic symptoms sub-dimensions were found to be positively associated with nomophobia. It was found that gender and subjective anxiety sub- dimension of anxiety scale significantly predicted nomophobia. On the other hand, it was found that the variable of age did not predict nomophobia significantly. The data obtained were discussed in the light of literature and suggestions were made to researchers.
Keywords: Nomophobia; Anxiety; University Students; Gender